(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
System of Education and Training is a major lever in the development of Morocco, this awareness has made this system as the second priority after national territorial integrity. Therefore, many projects have been implemented to reform the system of Education and Training. In this context, we discuss the National Charter of Education and Training representing the reference document benefiting from a general consensus for reform, the 2000-2010 decade was the decade of reform. The summary assessment of the reform shows that it is an " The Road Not Traveled "[1]. In order to accelerate reform of the System of Education and Training in Morocco, another program was designed and implemented for a period of four years from 2009 to 2012, this is the emergency program. Starting from the design phase, and based on the experiences and everyday practices of its implementation, the present article aims to answer the following questions with a target of capitalization of experiences and a contribution to make the Education System Training and learning organization: • How this program was developed? • What are the objectives of the program,? • What is it composed of? • How it works? • What arethe achievements? • Can we assess now? • What to donext? • What does theinformation represent inthis approach ? • What are the lessons we can draw?